Green synthesis, antimicrobial and antitumor activity of platinum nanoparticles: a review - Muraro, Pâmela Cristine Ladwig; Dos Anjos, Josiane Fontoura; Pinheiro, Lailla Daianna Soltau Missio; Gomes, Patrícia; Sagrillo, Michele Rorato; Da Silva, William Leonardo (Disciplinarum Scientia | Naturais e Tecnológicas, 2022)
Given the growing concern with environmental issues, the development of ecologically and economically viable technologies, with high yields and low cost, is essential. In this context, the green synthesis routes of metallic nanoparticles become relevant due to the use of biomolecules as a reducing agent to obtain nanoparticles. Platinum Nanoparticles (PtNPs) have some excellent properties such as high surface area and volume, high corrosion resistance, great anti-toxic and ecological activity. In this context, this study aims to show a review of the green synthesis of PtNPs and their antimicrobial and antitumor activity. The research was exploratory and qualitative using Scopus and Web of Science database. Thus, according to the articles, it can be concluded that the synthesis of green PtNPs is highly successful and that they have antimicrobial and antitumor activity.